Effectiveness and safety of nivolumab in advanced non-small cell lung cancer: The real-life data. (December 2018) - Dudnik, Elizabeth; Moskovitz, Mor; Daher, Sameh; Shamai, Sivan; Hanovich, Ekaterina; Grubstein, Ahuva; Shochat, Tzippy; Wollner, Mira; Bar, Jair; Merimsky, Ofer; Zer, Alona; Goldstein, Daniel A.; et al.
Highlights: This series illustrates treatment outcomes with nivolumab in a real life setting. The only variable which significantly correlated with OS was ECOG PS. mOS was 2.7 times shorter for ECOG PS ≥2 patients compared to ECOG PS 0/1 patients. Abstract: Objectives: Nivolumab has recently received regulatory approval as a 2nd-line treatment of non-small cell lung cancer (NSCLC). The data regarding its effectiveness and safety in real life setting is lacking. Materials and methods: 260 consecutive patients with advanced NSCLC treated with nivolumab at five Israeli cancer centers between January 2015 and March 2016 were evaluated for overall survival (OS) and toxicity. OS was analyzed by the Cox proportional-hazards regression model. Overall response rate (ORR) and progression-free survival (PFS) were assessed in 49 patients using RECIST, v.1.1. Results: Median age was 67y (41–99); males 68%; smokers 76%; ECOG PS ≥2 46%; non-squamous/squamous/other/NR 70%/23%/6%/1%; brain metastases 21%; liver metastases 21%; treatment line: 1st/2nd/3rd+-line/NR 6%/64%/26%/4%. With median survival follow-up of 18.5 months (range, 12.0–26.9), 155 (60%) patients died; median OS comprised 5.9 months (95% CI 4.7–7.4). In univariate and multivariate analysis, the only variable which significantly correlated with OS was ECOG PS. Median OS of patients with ECOG PS 0/1 and ECOG PS ≥2 comprised 9.5 months (95% CI, 6.7-NR) and 3.5 months (95% CI, 2.6–4.5), respectively. For 49 patients evaluable for response (median follow-up of 8.4 months (range, 2–16.8), ORR was 35%, median PFS was 2.8 months (95% CI, 1.8–7.7), incidence of pseudo-progression was 9%. The nivolumab safety profile was in accordance with the literature data, except for febrile neutropenia and pericarditis (observed in 1 case each). Conclusion: In real life setting, the effectiveness of nivolumab is reasonable yet less prominent than it has been demonstrated in clinical trials. ECOG PS ≥2 is associated with poor prognosis.